High inborn aerobic capacity does not protect the heart following myocardial infarction - Høydal, M. A. (American Physiological Society, 2013)
Maximal oxygen uptake (V̇o(2max)) is a strong prognostic marker for morbidity and mortality, but the cardio-protective effect of high inborn V̇o(2max) remains unresolved. We aimed to investigate whether rats with high inborn V̇o(2max) yield cardio-protection after myocardial infarction (MI) compared with rats with low inborn V̇o(2max). Rats breed for high capacity of running (HCR) or low capacity of running (LCR) were randomized into HCR-SH (sham), HCR-MI, LCR-SH, and LCR-MI. V̇o(2max) was lower in HCR-MI and LCR-MI compared with respective sham (P < 0.01), supported by a loss in global cardiac function, assessed by echocardiography. Fura 2-AM loaded cardiomyocyte experiments revealed that HCR-MI and LCR-MI decreased cardiomyocyte shortening (39%, and 34% reduction, respectively, both P < 0.01), lowered Ca(2+) transient amplitude (37%, P < 0.01, and 20% reduction, respectively), and reduced sarcoplasmic reticulum (SR) Ca(2+) content (both; 20%, P < 0.01) compared with respective sham. Diastolic Ca(2+) cycling was impaired in HCR-MI and LCR-MI evidenced by prolonged time to 50% Ca(2+) decay that was partly explained by the 47% (P < 0.01) and 44% (P < 0.05) decrease in SR Ca(2+)-ATPase Ca(2+) removal, respectively. SR Ca(2+) leak increased by 177% in HCR-MI (P < 0.01) and 67% in LCR-MI (P < 0.01), which was abolished by inhibition of Ca(2+)/calmodulin-dependent protein kinase II. This study demonstrates that the effect of MI in HCR rats was similar or even more pronounced on cardiac- and cardiomyocyte contractile function, as well as on Ca(2+) handling properties compared with observations in LCR. Thus our data do not support a cardio-protective effect of higher inborn aerobic capacity.